THE INDONESIAN CLASSROOM MANAGEMENT (An Ethnographic Study of Indonesian Classroom Behavior) - Muhammad Fatkhu Arifin (Universitas Ahmad Dahlan)
This study entitled “The Indonesian Classroom Management. It is purposed to answer the problem formulation that questioning about how the Indonesian classroom behaves, how Indonesian classrom is managed by the teacher, and how the confortable classroom look like based on the students’ perspective. This research used descriptive qualitative that describe the data that have been collected. The object of this study is the Indonesian classroom behaviour. The data were collected by observing the Indonesian classroom especially in English subject. The data collected were interpreted and described in the report. The result shows that Indonesian classroom has some behaviours such as; make a line before entering the class, praying before the class begin, singing the National Anthem, shaking the teachers’ hands whether in the begining and closing of the class, asking permission when to leave the class just for washing hands, praying after finish the whole activities in a day. In can be concluded from the result that Indonesian classroom has a very polite and orderly.